2017
DOI: 10.1038/srep43037
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of monolayer TMD WS2 and Raman study of substrate effects

Abstract: A facile transfer process for transition metal dichalcogenide WS2 flakes is reported and the effect of the underlying substrate on the flake properties is investigated using Raman spectroscopy. The flakes are transferred from their growth substrate using polymethyl methacrylate (PMMA) and a wet etch to allow the user to transfer the flakes to a final substrate using a microscope and micromanipulator combined with semi-transparent Kapton tape. The substrates used range from insulators such as industry standard … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
51
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 54 publications
4
51
0
Order By: Relevance
“…Studies of WS2 monolayers on different substrates have also shown changes in frequencies of up to 5 cm -1 for both the A1g and the E 1 2g modes depending on the substrate, at least partly due to strain. 71,76 The observed redshifts especially in our thicker films would imply a tensile strain. Regarding doping, a redshift of the A1g, and to a smaller degree of the E 1 2g mode, has been observed with increasing carrier concentration.…”
Section: Figurementioning
confidence: 76%
“…Studies of WS2 monolayers on different substrates have also shown changes in frequencies of up to 5 cm -1 for both the A1g and the E 1 2g modes depending on the substrate, at least partly due to strain. 71,76 The observed redshifts especially in our thicker films would imply a tensile strain. Regarding doping, a redshift of the A1g, and to a smaller degree of the E 1 2g mode, has been observed with increasing carrier concentration.…”
Section: Figurementioning
confidence: 76%
“…For Bi 2 Se 3 samples on SiO 2 , they were directly exfoliated onto the substrate. For samples on silicon nitride membranes, the Bi 2 Se 3 was exfoliated onto PMMA, then positioned and transferred onto a 100 nm thick membrane substrate using a micromanipulator and microscope method outlined in Mlack et al 30 . After positioning, acetone was used to remove the PMMA and complete the transfer of the Bi 2 Se 3 to the membrane.…”
Section: Nanostructure Transfermentioning
confidence: 99%
“…Like graphene, atomically thin WS 2 crystal is also a mechanically exceptional material, which can be grown or transferred on various substrates . On top of that, it is semiconductor, undergoing a transition from indirect to direct bandgap after thinning to monolayer .…”
Section: Introductionmentioning
confidence: 99%